Quiescent Fibroblasts Are More Active in Mounting Robust Inflammatory Responses Than Proliferative Fibroblasts - Chen, Bo-Rui (Public Library of Science, 2012)
Quiescent cells are considered to be dormant. However, recent studies suggest that quiescent fibroblasts possess active metabolic profile and certain functional characteristics. We previously observed that serum-starved quiescent fibroblasts respond to proinflammatory stimuli by robust expression of cyclooxygenase-2 (COX-2), which declines after the quiescent fibroblasts are driven to proliferation. In this study, we elucidated the underlying signaling and transcriptional mechanism and identified by microarray genes with similar differential expression. By using pharmacological inhibitors coupled with gene silencing, we uncovered the key role of protein kinase C δ (PKCδ) and extracellular signal regulated protein kinase 1/2 (ERK1/2) signaling in mediating COX-2 expression in quiescent cells. Surprisingly, COX-2 expression in proliferative cells was not blocked by PKCδ or ERK1/2 inhibitors due to intrinsic inhibition of PKCδ and ERK1/2 in proliferative cells. Restrained COX-2 transcription in proliferative cells was attributable to reduced NF-κB binding. Microarray analysis identified 35 genes whose expressions were more robust in quiescent than in proliferative cells. A majority of those genes belong to proinflammatory cytokines, chemokines, adhesive molecules and metalloproteinases, which require NF-κB for transcription. Quiescent fibroblasts had a higher migratory activity than proliferative fibroblasts as determined by the transwell assay. Selective COX-2 inhibition reduced migration which was restored by prostaglandin E(2). As COX-2 and inflammatory mediators induce DNA oxidation, we measured 8-hydroxydeoxyguanosine (8-OHdG) in quiescent vs. proliferative fibroblasts. PMA-induced 8-OHdG accumulation was significantly higher in quiescent than in proliferative fibroblasts. These findings indicate that quiescent fibroblasts (and probably other quiescent cells) are at the forefront in mounting inflammatory responses through expression of an array of proinflammatory genes via the PKCδ/ERK1/2 signaling pathway.